Lead exposure and its impact on the health of adolescents: the birth to twenty cohort - Naicker, Nisha (My University, 2013)
Introduction Lead exposure continues to be a major public health issue in South Africa, and other low and middle income countries. Environmental lead exposure has been associated with detrimental health effects in children. The aim of this thesis was to assess the prevalence of lead exposure and its association with various risk factors, its effects on puberty and socio-behavioural adjustment in adolescents. Methods The Birth to Twenty (Bt20) cohort study started in 1990, and is a long-term prospective follow-up study of children’s health and well-being. Mothers were recruited from antenatal clinics in the Johannesburg-Soweto metropolitan area between April and June 1990 (n=3273). Lead levels were analysed in samples of cord blood collected at birth (n=618) and whole venous blood collected at 13 years of age (n=1546). Data on selected child, maternal and household factors were collected using a structured questionnaire in the third trimester of pregnancy and at 13 years of age. Additional data on puberty (attainment of menarche and self-reported Tanner staging for breast and pubic development) and behaviour using the Youth Self Report was obtained at 13 years of age. Results In the Bt20 cohort the mean blood lead level at birth was 5.9 μg/dl, and at 13 years of age it was 5.7 μg/dl. The majority of children had blood lead levels above 5.0 μg/dl (52% at birth and 56% at 13 years). At birth, being a teenage mother and having low educational status were strong predictors for elevated cord blood lead levels. Being a male child, having an elevated cord blood level, and lack of household ownership of a phone were significant risk factors for high blood lead levels at 13 years. In 13 year old females with pubertal data (n= 682) the mean blood lead level was 4.9 μg/dl. Fifty percent had blood lead levels < 5.0 μg/dl, 49 % were ≥5.0 μg/dl and 1% was > 10.0 μg/dl. The average age of menarche was 12.7 years. At 13 years, 4% and 7% had reached Tanner stage 5 for pubic hair and breast development, respectively. Analyses showed that higher blood lead levels were significantly associated with delays in all measures of puberty (p <0.001). In the 13 year old sample with data on the Youth Self Report (n= 1041), the geometric mean blood lead level was significantly (P value<0.001) higher in boys (6.0 μg/dl) compared to girls (4.5 μg/dl). The bivariate analyses stratified by gender showed that boys’ blood lead levels were significantly associated with four types of aggressive behaviour. There were no significant associations found in girls. A multivariate analysis was conducted in the sample of boys and after adjusting for socio-economic factors ”Attacking People” remained significantly associated with blood lead levels. Conclusion Significant associations found in the study point to the low socio-economic status of lead exposed children. These poor circumstances frequently persist into adolescence resulting in continued high lead levels. Higher blood lead levels were associated with a delay in the onset of puberty in girls, and with anti-social behaviour among boys in early adolescence. Lead exposure in low and middle countries is generally higher compared to high income countries, and thus the effects of high blood levels are much greater and have larger personal and public health significance.
Keywords: Lead Poisoning; Adolescent; Environmental Pollutants